2001
DOI: 10.1038/35086520
|View full text |Cite
|
Sign up to set email alerts
|

In situ detection of collisionless reconnection in the Earth's magnetotail

Abstract: Magnetic reconnection is the process by which magnetic field lines of opposite polarity reconfigure to a lower-energy state, with the release of magnetic energy to the surroundings. Reconnection at the Earth's dayside magnetopause and in the magnetotail allows the solar wind into the magnetosphere. It begins in a small 'diffusion region', where a kink in the newly reconnected lines produces jets of plasma away from the region. Although plasma jets from reconnection have previously been reported, the physical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
466
4
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 516 publications
(497 citation statements)
references
References 25 publications
24
466
4
3
Order By: Relevance
“…There are fluctuations in B M in the exhaust but these variations are not consistent with the Hall field pattern, and their magnitude is substantially less then the 30-40% level (of the anti-parallel field) that had previously been reported in the vicinity of the X-line in the magnetosphere [e.g., Nagai et al, 2001;Øieroset et al, 2001]. This could suggest that the Hall field diminishes in strength with distance from the X-line.…”
Section: Reconnection Rate and The Location Of The X-linementioning
confidence: 49%
“…There are fluctuations in B M in the exhaust but these variations are not consistent with the Hall field pattern, and their magnitude is substantially less then the 30-40% level (of the anti-parallel field) that had previously been reported in the vicinity of the X-line in the magnetosphere [e.g., Nagai et al, 2001;Øieroset et al, 2001]. This could suggest that the Hall field diminishes in strength with distance from the X-line.…”
Section: Reconnection Rate and The Location Of The X-linementioning
confidence: 49%
“…Through magnetic reconnection, magnetic field lines of opposite polarity reconfigure to a lower energy state, with the release of magnetic energy as heat, directed plasma flow, and the penetration of the solar wind into the magnetosphere. Magnetic reconnection in the magnetotail has been observed by the Wind spacecraft in a serendipitous encounter, which has revealed the key processes predicted by the models [44].…”
Section: Testing Celeste3d Against the Gem Challengementioning
confidence: 99%
“…(43) and (44) can be compared: Their only difference lies in the term ∇∇ · E n+θ , which is replaced by −∇∇ · (µ · E n+θ ) in Eq. (44). In Eq.…”
Section: Temporal Discretizationmentioning
confidence: 99%
“…If a spacecraft flies through the ion diffusion region along the outflow direction, the expected large-scale signatures would be a reversal of plasma jetting, accompanied by a reversal of the normal component of the magnetic field. Coinciding with these reversals, one would also expect to detect portions of the quadrupolar out-of-plane Hall magnetic field (e.g., Oieroset et al 2001;Runov et al 2003;Borg et al 2005;Eastwood et al 2010aEastwood et al , 2010b) and bi-polar Hall electric field (Wygant et al 2005;Borg et al 2005;. Figure 1 displays an example of reported ion diffusion crossing by the Cluster spacecraft (Borg et al 2005) indicated by the reversals of the reconnection jets ( Fig.…”
Section: Magnetotailmentioning
confidence: 99%